Central banking in theory and practice - Blinder, Alan S. (The Lionel Robbins lectures, 1998)
Based on the 1996 Lionel Robbins Lectures, this book deals succinctly, in a nontechnical manner, with a wide variety of issues in monetary policy, including the goals of monetary policy, the choice of monetary instrument, the rule-versus-discretion debate, suggested remedies for the alleged problem of "inflationary bias," central bank credibility, arguments for and against central bank independence, and the interplay between the central bank and financial markets. The author examines each issue from the point of view of both an academic economist and a practicing policymaker - calling attention to the differences and similarities of perspective along the way.